2004
DOI: 10.1149/1.1645752
|View full text |Cite
|
Sign up to set email alerts
|

A Low-Cost, High Energy-Density Lead/Acid Battery

Abstract: Lightweight plastic grids for lead/acid battery plates have been prepared from acrylonitrile butadiene styrene copolymer. The grids have been coated with a conductive and corrosion-resistant tin oxide layer by a novel rapid thermally activated chemical reaction process. X-ray powder diffraction and X-ray photoelectron spectroscopy show the coated tin oxide film to be SnO 2 -like. The grids are about 75% lighter than conventional lead/acid battery grids. A 6 V/1 Ah lead/acid battery has been assembled and chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
19
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 9 publications
(16 reference statements)
1
19
0
1
Order By: Relevance
“…Accordingly, the cost of forming a corrosion-resistant coating on the grids by a sputtering process is likely to be high. Recently, Shivashankar et al 15,16 have employed a cost-effective, thermally activated chemical reaction process to produce tin-oxide-coated plastic grids for lead-acid batteries. Ironically, however, positive plates constituting tin oxide-coated grids have been found to be unstable in lead-acid batteries at 0.5 V vs. Pb/PbSO 4 electrode.…”
mentioning
confidence: 99%
“…Accordingly, the cost of forming a corrosion-resistant coating on the grids by a sputtering process is likely to be high. Recently, Shivashankar et al 15,16 have employed a cost-effective, thermally activated chemical reaction process to produce tin-oxide-coated plastic grids for lead-acid batteries. Ironically, however, positive plates constituting tin oxide-coated grids have been found to be unstable in lead-acid batteries at 0.5 V vs. Pb/PbSO 4 electrode.…”
mentioning
confidence: 99%
“…Therefore, the position of the protocell with DC output in the Ragone chart is depicted by a star ( * ) with dotted lines, indicating that depending on the droplet sizes, the same energy density may be delivered more slowly and at lower power density than the results based on a configuration calculated with droplets of 254 nL and 146 nL. The energy density of the DC protocell is ≈5% that of a lead-acid battery [82,83]; the power density of the DC protocell is comparable to traditional batteries. Compared with other alternative energy conversion devices (Figure 3), the electrogenic performance of protocells is much better than that of the piezoelectric devices and comparable to that of thermoelectric and photovoltaic devices.…”
Section: Power Density (W· Kgmentioning
confidence: 97%
“…The design optimized for maximum energy density output is estimated to produce 6.9 × 10 6 J·m −3 energy (≈1.92 W·h·kg −1 ), with an estimated energy conversion efficiency of 10%; the energy density is ≈5% that of a lead-acid battery [82,83]. The energy output calculated for a protocell optimally configured for high-energy density (6.92 × 10 6 J·m −3 ), with two pairs of droplets with diameters 3.9 cm and 3.3 cm, shows it could power a typical electronic gadget (≈20 mW) for about 10 h.…”
Section: Power Density (W· Kgmentioning
confidence: 99%
“…Similar studies to develop high specific energy leadacid batteries have also been reported. [7][8][9][10][11][12] More recently, Shivashankar et al 13,14 have employed a costeffective, thermally activated chemical reaction process to produce tin oxide-coated plastic grids for lead-acid batteries. Ironically, however, positive plates constituting tin oxide coated grids have been found to be unstable in lead-acid batteries at 0⋅5 V vs Pb/PbSO 4 electrode.…”
Section: Introductionmentioning
confidence: 99%
“…Ironically, however, positive plates constituting tin oxide coated grids have been found to be unstable in lead-acid batteries at 0⋅5 V vs Pb/PbSO 4 electrode. 13,14 Accordingly, it is desirable to find a room temperature process, to provide a corrosion-resistant coating on battery grids constituted from lightweight and inexpensive plastic materials, usually having a low-melting point.…”
Section: Introductionmentioning
confidence: 99%